Intra-articular vs. systemic administration of etanercept in antigen-induced arthritis in the temporomandibular joint. Part II: mandibular growth - Gelineck John; Pedersen Thomas K; Küseler Annelise; Kristensen Kasper D; Stoustrup Peter; Herlin Troels (BMC, 2009)
Abstract Background Temporomandibular joint (TMJ) arthritis in children causes alterations in the craniomandibular growth. Resultant abnormalities include; condylar erosions, a posterior mandibular rotation pattern, micrognathia, malocclusion with an anterior open bite, altered joint and muscular function occasionally associated with pain. These alterations may be prevented by early aggressive anti-inflammatory intervention. Previously, we have shown that intra-articular (IA) corticosteroid reduces TMJ inflammation but causes additional mandibular growth inhibition in young rabbits. Local blockage of TNF-α may be an alternative treatment approach against TMJ involvement in juvenile idiopathic arthritis (JIA). We evaluated the anti-inflammatory effect of IA etanercept compared to subcutaneous etanercept in antigen-induced TMJ-arthritis in young rabbits in terms of mandibular growth. This article (Part II) presents the data and discussion on the effects on facial growth. In Part I the anti-inflammatory effects of systemic and IA etanercept administration are discussed. Methods Arthritis was induced and maintained in the TMJs of 10-week old pre-sensitized rabbits (n = 42) by four repeated IA TMJ injections with ovalbumin, over a 12-week period. One group was treated weekly with systemic etanercept (0.8 mg/kg) (n = 14), another group (n = 14) received IA etanercept (0.1 mg/kg) bilaterally one week after induction of arthritis and one group (n = 14) served as an untreated arthritis group receiving IA TMJ saline injections. Head computerized tomographic scans were done before arthritis was induced and at the end of the study. Three small tantalum implants were inserted into the mandible, serving as stable landmarks for the super-impositions. Nineteen variables were evaluated in a mandibular growth analysis for inter-group differences. All data was evaluated blindedly. ANOVA and T-tests were applied for statistical evaluation using p < 0.05 as significance level. Results Significant larger mandibular growth disturbances were observed in the group receiving IA saline injections compared with the systemic etanercept group. The most pronounced unfavourable posterior mandibular rotation pattern was observed in the group receiving IA saline injections. Conclusion Intervention with systemic etanercept monotherapy equivalent to the recommended human dose allows a mandibular growth towards an original morphology in experimental TMJ arthritis. Systemic administrations of etanercept are superior to IA TMJ administration of etanercept in maintaining mandibular vertical growth.